Penggunaan Kahoot pada Pembelajaran Matematika: Systematic Literature Review - Lisra Mahfirah; Yahfizam (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The need to make an innovation to suport mathematics learning that is carried out online. One of the inovations that can be done is trough learning media. Learning media can be used to build ethuasiasm and motivation forstudents to learn which can improve learning learning outcomes. This study aims to conduct a literature review related to the use of Kahooot in mathematics learning. The research method chosen in this study is the SLR (Systematic Literature Review) method. Data collection was carried out by documenting and reviewing all articles related to the Kahoot application published in the 2012-2020 period. The articles used in this study were 27 articles from accredited national journals obtained from the Google Schoolar database using the Publish or Perish application. Based on this research, it was found that Kahoot could improve the result, ethusiasm for learning and the effectivennes of students in learning mathematics.